White Matter Correlates of Auditory Comprehension Outcomes in Chronic Post-Stroke Aphasia - Xing, Shihui; Lacey, Elizabeth H.; Skipper-Kallal, Laura M.; Zeng, Jinsheng; Turkeltaub, Peter E. (Frontiers in Neurology, 2017)
Neuroimaging studies have shown that speech comprehension involves a number of widely distributed regions within the frontal and temporal lobes. We aimed to examine the differential contributions of white matter connectivity to auditory word and sentence comprehension in chronic post-stroke aphasia. Structural and diffusion MRI data were acquired on 40 patients with chronic post-stroke aphasia. A battery of auditory word and sentence comprehension tests were administered to all the patients. Tract-based spatial statistics were used to identify areas in which white matter integrity related to specific comprehension deficits. Relevant tracts were reconstructed using probabilistic tractography in healthy older participants, and the mean values of fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD) of the entire tracts were examined in relation to comprehension scores. Anterior temporal white matter integrity loss and involvement of the uncinate fasciculus related to word-level comprehension deficits (RFA =0.408, P = 0.012; RMD = -0.429, P = 0.008; RAD = -0.424, P = 0.009; RRD =-0.439, P = 0.007). Posterior temporal white matter integrity loss and involvement of the inferior longitudinal fasciculus related to sentence-level comprehension deficits (RFA =0.382, P = 0.02; RMD = -0.461, P = 0.004; RAD = -0.457, P = 0.004; RRD =-0.453, P = 0.005). Loss of white matter integrity in the inferior fronto-occipital fasciculus related to both word- and sentence-level comprehension (word-level scores: RFA =0.41, P =0.012; RMD = -0.447, P = 0.006; RAD = -0.489, P = 0.002; RRD =-0.432, P = 0.008; sentence-level scores: RFA =0.409, P = 0.012; RMD = -0.413, P = 0.011; RAD = -0.408, P = 0.012; RRD =-0.413, P = 0.011). Lesion overlap, but not white matter integrity, in the arcuate fasciculus related to sentence-level comprehension deficits. These findings suggest that word-level comprehension outcomes in chronic post-stroke aphasia rely primarily on anterior temporal lobe pathways, whereas sentence-level comprehension relies on more widespread pathways including the posterior temporal lobe.